Teaching English vocabulary to adult learners (Journal of Pedagogical Inventions and Practices, 2021)
Teaching vocabulary is a vital part of any English language course. Many teachers are concerned about how to teach vocabulary. New words have to be introduced in such a way as to capture the students’ attention and place the words in their memories.